Design and fabrication of a low-cost coil winding machine for slotless toroidal stators (LACCEI, 2024)
Slotless axial flux permanent magnet machines, so-called Torus, are particularly suitable for applications that require short axial length and a high power-to-weight ratio. The ease of construction of the slotless toroidal stator core enables the use of highly efficient amorphous and nanocrystalline alloys. However, winding the coils requires either a specific winding machine -which can be too expensive at a prototyping stage-, a purely manual process -which is highly tedious and inefficient-, or a cut ferromagnetic core to insert the pieces into pre-wound coils -which deteriorates the magnetic properties of the toroidal stator core-. Here, we demonstrate a winding technology suited for Torus’ stator prototypes. The device transfers the wire from the primary copper spool onto a secondary circular spool and then unwinds it onto the toroidal core. We designed 3D-printed accessories to achieve coils with good accuracy and repeatability. Our Torus winding machine is easy to build and use, and yet keeps the prototyping process cost low.